2019
DOI: 10.3390/ijms21010274
|View full text |Cite
|
Sign up to set email alerts
|

The Use of High-Throughput Transcriptomics to Identify Pathways with Therapeutic Significance in Podocytes

Abstract: Podocytes have a unique structure that supports glomerular filtration function, and many glomerular diseases result in loss of this structure, leading to podocyte dysfunction and ESRD (end stage renal disease). These structural and functional changes involve a complex set of molecular and cellular mechanisms that remain poorly understood. To understand the molecular signature of podocyte injury, we performed transcriptome analysis of cultured human podocytes injured either with PAN (puromycin aminonucleoside) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…Consistent with this analysis, E11 cells with miR-217-5p overexpression exhibited shrunken cell shapes with shortened or disorganized actin cytoskeletons. Previously, Solanki et al demonstrated that the apoptosis-related p53 pathway is involved in actin cytoskeleton damage in PAN-or ADR-treated podocytes [36]. However, in our study, the p53 pathway was not associated with predicted targets of miR-217-5p in PAN-treated podocytes.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Consistent with this analysis, E11 cells with miR-217-5p overexpression exhibited shrunken cell shapes with shortened or disorganized actin cytoskeletons. Previously, Solanki et al demonstrated that the apoptosis-related p53 pathway is involved in actin cytoskeleton damage in PAN-or ADR-treated podocytes [36]. However, in our study, the p53 pathway was not associated with predicted targets of miR-217-5p in PAN-treated podocytes.…”
Section: Discussioncontrasting
confidence: 88%
“…This possibility was supported by analyses of publicly available datasets of podocyte injury-related transcriptomes. The analysis of the dataset GSE124622, created through microarray analysis of immortalized human podocytes treated with PAN and Adriamycin (ADR) to cause podocyte injury [36], showed that Myo1d mRNA levels in the PAN-and ADR-treated podocytes decreased 0.41-fold (p = 7.54E-06) and 0.64-fold (p = 0.0364) compared to control podocytes, respectively (Table S5). Furthermore, analysis of the dataset GSE108629 analysis, created through a microarray-based study using a mouse model of immunotoxin-inducible podocyte injury, showed that Myo1d mRNA levels were reduced 0.61-fold (p = 0.00158) after podocyte injury [37].…”
Section: Gene Ontologies Associated With the Predicted Targets Of The...mentioning
confidence: 99%
“…PPARγ binds to its promoter response elements (PPRE) along with other transcription factors such as retinoid X receptor (RXR) or to other DNA elements in association with factors such as nuclear factor kappa B (NFκB), activator protein 1 (AP1), and in proximity to CCAAT enhancer-binding proteins (C/EBPα) [5, 24, 38]. We carried out promoter element prediction using a PPARgene database (ppargene.org) [43] and cross-referenced it with bulk RNASeq GEO datasets obtained from control podocytes (GSE124622) [41] and adipocytes (GSE129153) [42]. We found that while 1669 PPRE-containing genes were detectable in both podocyte and adipocyte datasets, 453 were found to be unique to podocytes and 77 unique to adipocytes (Figure 3Ai, Supplementary Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Since injury to podocytes is known to induce NEPHRIN and NEPH1 phosphorylation ( 3 , 8 , 30 ), we hypothesized that NEPHRIN and NEPH1 phosphorylation may require the downregulation of SHP-2 expression. Indeed, mRNA profiling of cultured podocytes injured by the puromycin amino nucleoside (Gene Expression Omnibus accession number GSE124622 ( 31 )) showed a 5-fold reduction in SHP-2 expression ( Fig. S5 ).…”
Section: Discussionmentioning
confidence: 99%